Deficiency of IKKβ in neurons ameliorates Alzheimer's disease pathology in APP‐ and tau‐transgenic mice. Issue 2 (23rd January 2023) - Schnöder, Laura; Quan, Wenqiang; Yu, Ye; Tomic, Inge; Luo, Qinghua; Hao, Wenlin; Peng, Guoping; Li, Dong; Fassbender, Klaus; Liu, Yang
Abstract: In Alzheimer's disease (AD) brain, inflammatory activation regulates protein levels of amyloid‐β‐peptide (Aβ) and phosphorylated tau (p‐tau), as well as neurodegeneration; however, the regulatory mechanisms remain unclear. We constructed APP‐ and tau‐transgenic AD mice with deletion of IKKβ specifically in neurons, and observed that IKKβ deficiency reduced cerebral Aβ and p‐tau, and modified inflammatory activation in both AD mice. However, neuronal deficiency of IKKβ decreased apoptosis and maintained synaptic proteins (e.g., PSD‐95 and Munc18‐1) in the brain and improved cognitive function only in APP‐transgenic mice, but not in tau‐transgenic mice. Additionally, IKKβ deficiency decreased BACE1 protein and activity in APP‐transgenic mouse brain and cultured SH‐SY5Y cells. IKKβ deficiency increased expression of PP2A catalytic subunit isoform A, an enzyme dephosphorylating cerebral p‐tau, in the brain of tau‐transgenic mice. Interestingly, deficiency of IKKβ in neurons enhanced autophagy as indicated by the increased ratio of LC3B‐II/I in brains of both APP‐ and tau‐transgenic mice. Thus, IKKβ deficiency in neurons ameliorates AD‐associated pathology in APP‐ and tau‐transgenic mice, perhaps by decreasing Aβ production, increasing p‐tau dephosphorylation, and promoting autophagy‐mediated degradation of BACE1 and p‐tau aggregates in the brain. However, IKKβ deficiency differently protects neurons in APP‐ and tau‐transgenic mice. Further studies are needed, particularly in the context of interaction between Aβ and p‐tau, before IKKβ/NF‐κB can be targeted for AD therapies.